Adoption of mobile commerce: the impact of end user satisfaction on system acceptance - Ghobakhloo, Morteza; Tang, Sai Hong; Zulkifli, Norzima (IGI Global, 2013)
Although voluntary individual usage behavior of information system and technology is well studied in the literature, further theoretical development is needed to account for the specific characteristics of the mobile commerce. This study presents an extended technology acceptance and satisfaction model presented by Wixom and Todd (2005) that integrates technology acceptance and technology satisfaction into unified model to investigate what determines user mobile commerce acceptance and usage. The contributions of this paper are to extend and adapt the user satisfaction and technology acceptance model in an empirical study of 503 mobile commerce users, shedding light on the significance and relative importance of specific acceptance and satisfaction factors. This study validates the user satisfaction and technology acceptance model in business to customer mobile commerce context. The implication of this study to both researchers and practitioners is discussed.